PEMBERDAYAAN INDUSTRI KECIL ANYAMAN BAMBU DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DESA KARAYUNAN KECAMATAN CIGASONG KABUPATEN MAJALENGKA PROVINSI JAWA BARAT - Juliarti Prihatini (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
The empowerment of small industry of woven bamboo craftsmen in the village of Karayunan that is carried out by the Department of Small and Medium Enterprises Group of Industry and Trade ofMajalengka District has not been optimal. Therefore, the department seeks (1) to make an increaseof access and market share, which are promotion and information, giving an aid in supplying theproduction tolls; (2) to engage in the exhibition; (3) to make a socialization of Training Center and (4)to conduct motivation skills training such as a small industry of food in the district of Majalengka. Therole of small industry of woven bamboo is sufﬁ ciently increased people’s incomes, this thing can be seenfrom the employment. The inhibiting factors of the empowerment of small industry of woven bamboocraftsmen are the limited fund; still using simple equipments; lack of marketing and lack of educationof the craftsmen and work force.